2020
DOI: 10.1021/acsapm.0c00183
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Poly(hydroxyurethane)s with Multiwalled Carbon Nanotubes: Synthesis, Shape Memory, and Reprocessing Properties

Abstract: Poly­(hydroxyurethane)­s (PHUs) are synthesized via non-isocyanate approaches and could be the potential alternatives of conventional polyurethanes. It is of importance to investigate the structure–property relationship of PHUs. In this work, we investigated the PHU nanocomposites containing multiwalled carbon nanotubes (CNTs). First, CNTs were functionalized with poly­(acryloyl carbonate), a polymer bearing 6-membered cyclic carbonate groups (denoted PA6CC) via the surface reversible addition–fragmentation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…The incorporation of inorganics in organic polymers is an important technique to develop materials with excellent comprehensive properties. Recently, organic-inorganic nanocomposites of PHU with various inorganic nanoparticles have been also reported; the nanocomposites possess enhanced thermal, mechanical properties, and other specific properties [ 37 , 38 , 39 , 40 ]. For instance, Zheng et al [ 37 ] reported PHU/carbon nanotubes (CNTs) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of inorganics in organic polymers is an important technique to develop materials with excellent comprehensive properties. Recently, organic-inorganic nanocomposites of PHU with various inorganic nanoparticles have been also reported; the nanocomposites possess enhanced thermal, mechanical properties, and other specific properties [ 37 , 38 , 39 , 40 ]. For instance, Zheng et al [ 37 ] reported PHU/carbon nanotubes (CNTs) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic-inorganic nanocomposites of PHU with various inorganic nanoparticles have been also reported; the nanocomposites possess enhanced thermal, mechanical properties, and other specific properties [ 37 , 38 , 39 , 40 ]. For instance, Zheng et al [ 37 ] reported PHU/carbon nanotubes (CNTs) nanocomposites. Notably, the incorporation of CNTs significantly improved the mechanical and dielectric properties of PHU.…”
Section: Introductionmentioning
confidence: 99%
“…This crosslinking strategy is in marked contrast to those to crosslink PTUs (or PHUs) with multifunctional amines or cyclic carbonates as the crosslinkers. [ 21–27 ] Shown in Figure are the Fourier transform infrared (FTIR) spectra of 1 , PMTU‐PPO430, c ‐PTU‐PPO430, and the recovered PTMU‐PPO430 with sodium l ‐ascorbate. For 1 , the stretching vibration of SC< bond was detected at 1736 cm −1 and that of the S–C–S linkage occurred at 1674 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the chemistries, structures, and properties of PHUs have been extensively investigated. [ 10–27 ] Of cyclic carbonates that are used to obtain PHUs, five‐membered cyclic monomers are readily synthesized via the reaction of epoxides with carbon dioxide (CO 2 ) with high yields. [ 6–8 ] Similarly, carbon sulfide (CS 2 ) can be used to synthesize five‐membered cyclic carbonates with its reaction with epoxide groups.…”
Section: Introductionmentioning
confidence: 99%
“…[76]Moreover, the reversibility of the hydroxyurethane linkage formed by TAEA is even easier compare to other amines and may occur at relatively low temperatures. [77,78] Additionally, a small amount of unreacted TAEA may be present in the material. On the other hand, the cross-linked copolymers with higher BA ratios exhibited higher 5% weight loss temperature values, following the same behavior that the uncured copolymers and previously observed by Kumar Konaganti et al [74] for BA/MMA copolymers.…”
Section: Resultsmentioning
confidence: 99%